2017
DOI: 10.1002/solr.201700048
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic CsPbI3 Perovskite‐Based Solar Cells: A Choice for a Tandem Device

Abstract: Hygroscopicity risk and organic-inorganic hybrid perovskites easy decomposition in solar cells limit their usefulness. Apart from the hybrid organicinorganic perovskites, inorganic perovskite solar cells display a better stability toward moisture, light soaking, and thermal stressing. However, most inorganic perovskites are inappropriate for single junction or tandem solar cells due to their large bandgaps (>1.8 eV), which eventually results in light absorption loss. Fortunately, cubic CsPbI 3 perovskite (havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
239
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(244 citation statements)
references
References 59 publications
(79 reference statements)
4
239
0
1
Order By: Relevance
“…Later, the dual halide CsPbI 2 Br was developed, and it has great advantages in terms of ambient phase stability and a more suitable band gap (1.91 eV) . Further study confirmed that the desired black phase CsPbI 2 Br is indeed tolerant to a range of degradation factors; however, it turns into the non‐perovskite orthorhombic phase upon exposure to a humid environment or water vapor . Hence, it is imperative to protect it against moisture ingress.…”
Section: Comparison Of Parameters For Pscs Based On Cspbi2br Films Momentioning
confidence: 99%
“…Later, the dual halide CsPbI 2 Br was developed, and it has great advantages in terms of ambient phase stability and a more suitable band gap (1.91 eV) . Further study confirmed that the desired black phase CsPbI 2 Br is indeed tolerant to a range of degradation factors; however, it turns into the non‐perovskite orthorhombic phase upon exposure to a humid environment or water vapor . Hence, it is imperative to protect it against moisture ingress.…”
Section: Comparison Of Parameters For Pscs Based On Cspbi2br Films Momentioning
confidence: 99%
“…For this reason, all‐inorganic halide perovskites formed by substituting the organic cation with cesium (Cs) have become promising alternative candidates because of their inherent thermodynamic stability . Among these perovskites, black‐phase cesium lead iodide (CsPbI 3 ) has recently attracted great attention because of its excellent thermal stability and suitable optical bandgap (≈1.73 eV), which make it an ideal material for application in tandem cells combined with low‐bandgap photovoltaic materials . Nevertheless, the all‐inorganic CsPbI 3 perovskite without any volatile organic component faces serious challenges in terms of low‐phase stability.…”
Section: Introductionmentioning
confidence: 99%
“…A solution to this impasse is to replace organic cations with inorganic cesium ion (Cs + ) to form cesium lead halide (CsPbX 3 , X = I, Br, Cl) light‐harvesters . Among these inorganic perovskites, CsPbI 3 has a more suitable bandgap of 1.73 eV, however, the notorious stability under low‐temperature and air‐atmosphere lead to the inferior performance . Till now, enormous efforts have proved that reducing iodide dosage of perovskite film can significantly improve the durability and photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%